2002
DOI: 10.1089/08977150260139129
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Titers of Proinflammatory Cytokines and CNS Autoantibodies in Patients with Chronic Spinal Cord Injury

Abstract: This study characterized the proinflammatory cytokines, interleukin-2 (IL-2) and tumor necrosis factor alpha (TNFalpha), the antiinflammatory cytokines, IL-4 and IL-10, autoantibodies specific for GM1 ganglioside (anti-GM1), IgG and IgM, and myelin-associated glycoprotein (anti-MAG), in the sera of infection-free, chronic (>12 months), traumatically injured SCI patients (n = 24). Healthy able-bodied subjects (n = 26) served as controls. The proinflammatory cytokines and anti-GM1 antibodies were of particular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(128 citation statements)
references
References 54 publications
4
123
0
1
Order By: Relevance
“…This results in the accumulation of stagnant urine within the bladder, allowing for an increase in bacterial growth and a resulting risk of infection. 2 UTIs have been consistently shown to be the most frequent cause of re-hospitalization in the SCI population, accounting for~24-54% of cases. 32 This indicates that UTIs are a common occurrence, not only during the acute stages of SCI but also in the long term as well.…”
Section: Somatic Nerve Damagementioning
confidence: 99%
See 2 more Smart Citations
“…This results in the accumulation of stagnant urine within the bladder, allowing for an increase in bacterial growth and a resulting risk of infection. 2 UTIs have been consistently shown to be the most frequent cause of re-hospitalization in the SCI population, accounting for~24-54% of cases. 32 This indicates that UTIs are a common occurrence, not only during the acute stages of SCI but also in the long term as well.…”
Section: Somatic Nerve Damagementioning
confidence: 99%
“…As such, various areas of the body, particularly the gluteal and sacral regions, may be at risk for oxygen deprivation and necrosis. 2 Individuals with SCI are at a particularly high risk for pressure ulcer development with~40% of individuals developing a pressure sore within any three-year period. 32 Acute secondary health complications such as these result in an acute inflammatory response characterized by a spike in proinflammatory mediators.…”
Section: Somatic Nerve Damagementioning
confidence: 99%
See 1 more Smart Citation
“…The TNF-α levels were significantly elevated following an initial decrease in concentration in the first 12 h after injury. Although studies have shown increased IL-1β and TNF-α after SCI, 11,12 this was the first study to have taken repeated measurements over time to generate a temporal cytokine profile for IL-1β and TNF-α in humans. Because of the not especially large patient collective (n = 23), there were associated differences in absolute values with a high and variable s.d.…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Previously, it has been reported that cytokines induce the systemic overproduction of autoantibody. 54,55 In this context, the production of PGI 2 receptor-specific antibody might be called possibly, in part, an 'auto-immune' condition proved by injury to the spinal cord or related to secondary inflammatory conditions, such as, chronic pressure ulcers and/ or low grade infections of the bladder or respiratory tract.…”
Section: Similarity Of the Insulin And Pgi 2 Receptorsmentioning
confidence: 99%